2018
DOI: 10.1093/infdis/jiy150
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review: Performance of Rapid Diagnostic Tests for the Detection of Plasmodium knowlesi, Plasmodium malariae, and Plasmodium ovale Monoinfections in Human Blood

Abstract: This work summarizes the available data on the performance of rapid diagnostic tests (RDTs) for the detection of monoinfections due to Plasmodium species P. knowlesi, P. malariae, and P. ovale and indicates low performance of RDTs to detect these infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 63 publications
1
39
0
3
Order By: Relevance
“…LDH can be divided into three categories: Pf-specific, Pv-specific and pan-specific. Antibodies against these antigens can be combined in one type of RDTs to detect different Plasmodium species [9,10]. According to Bell and his colleagues, RDTs can be divided into 7 types depending on their target antigens (Appendix S1 in the Online Supplementary Document) [11].…”
Section: Viewpoints Papersmentioning
confidence: 99%
“…LDH can be divided into three categories: Pf-specific, Pv-specific and pan-specific. Antibodies against these antigens can be combined in one type of RDTs to detect different Plasmodium species [9,10]. According to Bell and his colleagues, RDTs can be divided into 7 types depending on their target antigens (Appendix S1 in the Online Supplementary Document) [11].…”
Section: Viewpoints Papersmentioning
confidence: 99%
“…A previous systematic review of 33 articles published between 1922 and 2015 demonstrated that a total of five out of 22 severe cases of P. ovale malaria were fatal, and two cases of congenital P. ovale malaria were fatal [29]. A more recent systematic review conducted by Yerlikaya et al in 2018 demonstrated that a RDT had poor performance in detecting P. ovale because P. ovale infections usually occur at very low parasite densities, leading to missed detection by microscopy and RDTs [30]. Nevertheless, studies on the prevalence of severe P. ovale malaria provide more information on this neglected species and are urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of RDTs for detecting knowlesi malaria has not been thoroughly investigated, but their sensitivity is known to be suboptimal. 5,6 In a recent systematic review, although the accumulated evidence is not sufficient, the overall sensitivity varied between 2% and 48% depending on the RDT kit used. 6 The RDT kit which we used for this patient targets histidine-rich protein 2, specific to Plasmodium falciparum, and aldolase, a panmalarial antigen.…”
Section: Discussionmentioning
confidence: 99%